Rapid preparation method of ternary nitride
By charging the ternary metal salt and sodium amino in a layered manner under high-pressure sealing conditions, the problems of low synthesis efficiency and product purity in ternary nitride synthesis were successfully solved, and the rapid preparation of high-quality ternary nitrides was achieved.
Patent Information
- Application Number
- CN202510087965.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-04-18
Smart Images

Figure CN119838505A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of metal nitride preparation, and specifically relates to a rapid preparation method of ternary nitride. Background Art
[0002] Ternary nitride materials were first demonstrated through bulk synthesis, and these techniques have played an important role in the development of this class of materials. Bulk synthesis techniques can control crystallization and cation ordering, allowing the discovery of materials that may not be possible in thin films. Bulk synthesis can be divided into two cases: one is carried out in an open system, that is, under constant chemical potential μ(N) conditions, when the N source is actually infinite; the other is carried out in a closed system, where the N source is finite, so μ(N) may change during the reaction.
[0003] At present, there are two main mature processes for preparing ternary nitrides: one is the amination method using metals and metal salts in an open atmosphere (i.e., under normal pressure), and the other is the high-temperature chemical reaction of binary nitride precursors in a closed atmosphere. For the former method, since ternary nitrides usually have a metastable structure under normal pressure, their formation temperature is generally higher than the decomposition temperature. Therefore, the prepared ternary nitrides often have a nano-morphology with poor crystallinity and are generally in a denitrified phase.
[0004] When synthesized in an open system, vapor-phase nitridation of the precursor with a N source is usually required. For highly electropositive lanthanum (Ln) series or early transition metals (TM), the oxidizing property of N2 is sufficient to satisfy the formation of nitrides, such as the synthesis of LnSi3N5 using dual-phase Ln series Si alloys or the synthesis of MgMoN2 from the reaction of N2 with Mg3N2 and Mo. Although in an open system, active nitrogen-containing precursors can maintain sufficient μ(N) under conditions close to ambient nitrogen and ammonia partial pressures to promote the synthesis of nitrides. However, in all open system cases, it is still very difficult to react highly electronegative metals (such as tin) or avoid the addition of oxygen impurities without special purification procedures.
[0005] Closed systems are particularly suitable for the re-reaction of binary nitrides, in which all the required N2 is contained in the precursor. The reaction of binary nitrides is usually carried out in welded refractory metal tubes to avoid reactions between the metal and other containers. However, the synthesis of ternary nitrides in a closed system usually has the following problems: (1) Since it is impossible to maintain sufficient μ(N), the amount of raw materials for a single reaction in the closed system synthesis of ternary nitrides is limited, resulting in extremely low synthesis efficiency; (2) During the synthesis process, μ(N) will also cause a gradient change, that is, the μ(N) in the area where the reaction occurs preferentially will gradually become lower than that in the area far away from the reaction as the reaction time increases, resulting in the inability to continue the reaction; (3) The reaction is not complete, and usually by-products remain in the product, resulting in low product purity.
[0006] An effective method for preparing ternary nitride crystals in a closed system and under extreme pressure is to perform an ammoniacal reaction in a specially designed melt chamber. By using corrosion-resistant and high-temperature-resistant alloys (such as nickel-based superalloys), the reaction can be carried out in supercritical NH3 at high temperatures (>600 °C) and high pressures (>600 MPa or 6 kbar). The high-flowability high-μ(N) supercritical fluid provides an ideal environment for synthesis, and the solution chemistry can be controlled by using various mineralizers (such as acidic NH4 X ; Alkaline A NH2) can be adjusted. This adjustment is critical to the successful synthesis of ternary nitrides and can be used to promote or suppress the generation of intermediates or defects (e.g., mixed metal amides and hydrides). Supercritical ammonia nitrogen methods have been used with the alkaline mineralizer KNH2 to synthesize ZnSiN2 and ZnGeN2, and evidence of cation ordering can be obtained under conditions of T = 870-1070 K and P < 230 MPa or 2.3 kbar. These methods are well suited for basic research and exploratory syntheses requiring high-quality single crystals. However, they have not been widely adopted due to the high cost and expertise required to reduce the hazardousness of these processes. In contrast, multi-faceted anvil presses (such as the six-sided top press), although also expensive, are less hazardous. At T>1000 K, μ(N) is above kMPa-level hydrostatic pressures [μ-μ(T0, P0)>0 eV / atom], and the extreme temperatures and pressures also increase the solid-state diffusion required for crystallization and cation ordering of many ternary nitrides. For example, when ZnCl2, Si3N4 and LiN3 segregate in a tantalum tube welded at 700℃, a cation-ordered Pn When 21-ZnSiN2 nanocrystals are prepared, annealing at 6 GPa and 1200 °C is required to fully crystallize the material. In some cases, the precursors need to be properly selected to ensure atomic-scale mixing of the reactions, such as the partial synthesis of fluoride salt precursors at 5 GPa to crystallize ZnSnN2.
[0007] Since the synthesis of ternary nitrides is a relatively shallow research field, its development still faces great challenges. Existing synthesis methods span different μ (N) value ranges, but the increase in temperature is still necessary for mass transfer in bulk synthesis methods. At present, how to choose the right precursor and preparation process is still a difficulty in the rapid preparation of high-quality ternary nitrides. Summary of the invention
[0008] The object of the present invention is to overcome at least one disadvantage of the prior art and provide a method for rapidly preparing ternary nitrides.
[0009] The technical solution adopted by the present invention is: In a first aspect, the present invention provides a method for rapidly preparing a ternary nitride, comprising the following steps: charging a ternary metal salt and an excess of sodium amide in a layered manner of ternary metal salt-sodium amide-ternary metal salt, and then reacting at a pressure of 1 to 6 GPa to obtain a ternary nitride crystal corresponding to the ternary metal salt.
[0010] In some examples, the molar ratio of the ternary metal salt-sodium amide-ternary metal salt layer is 2.5:(1-1.05):2.5.
[0011] In some examples, the diameter of the contact surface between each layer of the ternary metal salt-sodium amide-ternary metal salt is less than 10 mm.
[0012] In some examples, the ternary metal salt is selected from FeWO4 or FeMoO4.
[0013] In some examples, the reaction pressure is 2-5 GPa; and / or the reaction temperature is 800-1800°C.
[0014] In some examples, the reaction time is 1 to 5 min.
[0015] In some examples, the reactants are charged into a heat-resistant tube that does not participate in the reaction.
[0016] In some examples, the heat-resistant tube is selected from a salt tube and a hexagonal boron nitride tube.
[0017] In some examples, the wall thickness of the heat-resistant tube is greater than 1 mm.
[0018] In some examples, the size of the prepared ternary nitride crystals is 1-50 μm.
[0019] The beneficial effects of the present invention are: The high-pressure sealing method used in the present invention can effectively inhibit the decomposition of the ternary nitride product, thereby synthesizing a crystal with high quality and in accordance with the stoichiometric ratio, and even obtaining a single crystal sample. Compared with the traditional high-pressure sealing method, we use a ternary metal oxide salt (ABO x ) as the metal source and sodium amide (NaNH2) as the solid nitrogen source, which can effectively reduce the temperature required for synthesis and improve mass transfer. This not only improves the efficiency and stability of the synthesis experiment, but also reduces the experimental cost. Compared with the traditional method of using chloride salt as the metal salt, the reaction rate can be effectively controlled, reducing the risk of violent reaction of the sample during the assembly process and avoiding the risk of "explosion" of the press due to violent heat release during the reaction. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a schematic diagram of the high-pressure chamber assembly required for the synthesis of ternary nitrides. Note: 1- six-sided top press WC hammer, 2- pyrophyllite assembly block, 3- salt tube.
[0021] Figure 2 XRD spectra of the products (a) FeWN2 and (b) FeMoN2 obtained at different synthesis temperatures under 3 GPa pressure.
[0022] Figure 3 The following are XRD spectra of a series of ternary nitrides prepared by the method of the present invention.
[0023] Figure 4 SEM images of the products (a) FeWN2 and (b) FeMoN2 obtained by assembling the raw materials in a layered manner at a pressure of 3 GPa and a synthesis temperature of 1200 °C.
[0024] Figure 5 SEM images of the products (a) FeWN2 and (b) FeMoN2 obtained by assembling the raw materials in a mixed manner, at a pressure of 3 GPa and a synthesis temperature of 1200 °C.
[0025] Figure 6 Zero-field cooling and field-cooling curves of (a) FeWN2 and (b) FeMoN2 synthesized by high temperature and high pressure.
[0026] Figure 7 The inverse of the magnetic susceptibility of (a) FeWN2 and (b) FeMoN2 synthesized by high temperature and high pressure.
[0027] Figure 8 The effective magnetic moments of (a) FeWN2 and (b) FeMoN2 synthesized under high temperature and high pressure. DETAILED DESCRIPTION
[0028] The following disclosure provides many different embodiments or examples for implementing different solutions of the present invention.
[0029] The present invention adopts a high temperature and high pressure method to prepare ternary nitrides. This paper takes the synthesis of FeWN2 and FeMoN2 as examples for description. Figure 1 The schematic diagram of the high-pressure chamber assembly required for the synthesis of ternary nitrides is shown. The experiment was carried out on a six-sided top press device (DS650). First, the metal oxide salts (i.e., FeWO4 and FeMoO4) and sodium amide (NaNH2) with a stoichiometric ratio of 1:5 are pre-pressed into tablets. The layering method of ternary metal salt-sodium amide-ternary metal salt needs to be symmetrically loaded according to the chemical molar ratio of 2.5:1:2.5, and the contact surface is controlled to be less than Φ10 mm (i.e., the inner diameter of the sodium chloride tube used in the present invention). If the size of the reaction chamber is too large, the contact area can be appropriately reduced. Then place it in the salt tube in a sandwich stacking manner (i.e. Figure 1 3). We use layered assembly of raw materials, which can reduce the reaction rate and greatly improve the safety of the experiment. On the other hand, it reduces the contact area of the reactants to reduce the nucleation amount of the target product, which provides favorable thermal and kinetic conditions for the growth of crystal size (that is, it can continuously transport raw materials to the interface during the insulation process and provide an enriched environment for raw materials). Then, the salt (NaCl) tube and the high-pressure assembly block ( Figure 1 The other parts are assembled together and finally placed on the WC hammer ( Figure 1 The pressure is increased to 3 GPa. Then it is heated to 500-1200℃, kept at this temperature for 5 minutes, and quickly cooled to room temperature. The excessive amount of NaNH2 is to provide a nitrogen-rich atmosphere to avoid the occurrence of denitrification. It should be noted that the high-pressure assembly is completed in a glove box filled with an inert atmosphere to prevent NaNH2 from contacting and reacting with water in the air. x B y O z ) is obtained by uniformly mixing Fe2O3 (Mo2O3) and WO3 in a stoichiometric ratio of 1:2.1 and calcining in a muffle furnace at 1000 °C for 3 hours. The chemical reaction is shown in equation (1). The excess WO3 is to compensate for the volatilization loss of WO3 at high temperature.
[0030] Fe2O3 (Mo2O3) + WO3 → FeWO4 (FeMoO4) (1) When the sample was taken out from the high-pressure assembly after decompression, a pungent ammonia smell was smelled. This indicates that during the high-temperature and high-pressure reaction, NaNH2 decomposed to produce ammonia gas and provided the required nitrogen source for the reaction. The salt tube after the reaction was placed in a beaker and washed with pure water to remove excess sodium amide and by-product sodium hydroxide, and finally a black product was obtained. The reaction equation is shown in formula (2).
[0031] FeWO4(FeMoO4)+ 5NaNH2 FeWN2(FeMoN2)+NaOH + NH3(2) In order to confirm the phase of the product, we performed X-ray diffraction (XRD) analysis on the product. Figure 2 (a) shows the XRD spectrum of the product obtained by heating FeWO4 and NaNH2 at 500-1200 ℃ for 5 minutes under 3GPa pressure. At lower synthesis temperatures (below 800 ℃), only rhombohedral R-W2N3 binary nitride and unknown phases can be obtained. As the synthesis temperature increases, a pure phase with hexagonal symmetry is obtained at 800-1200 ℃, and the width of the diffraction peak decreases with increasing temperature, indicating that the crystallinity of the sample is improved. By comparing with the standard card, it was determined that the product is a pure phase. P 63 / mm c Symmetry FeWN2 and FeMoN2 ( Figure 2 (b)). By this method, we also prepared a series of MnWN2, MnMoN2, MgMoN2 and MgWN2 with P 63 / mm The XRD spectrum of the ternary nitride with c symmetry is as follows Figure 3 shown.
[0032] In order to characterize its morphology and crystallinity, we performed scanning electron microscopy on the samples obtained at a synthesis temperature of 1200 °C, such as Figure 4 As shown. Due to the layered loading method, the product shows a clear size gradient. It is worth noting that the maximum size of the FeWN2 sample can reach 50 μm ( Figure 4 (as shown in (a)), has a typical hexagonal crystallographic morphology, corresponding to its hexagonal symmetry, and the minimum size is more than 1 μm, which is much higher than the crystallinity of samples prepared by previously reported methods. Although the crystallinity of FeMoN2 is slightly worse than that of FeWN2, its maximum grain size reaches 10 μm, which is also much higher than the crystallinity of samples prepared by other methods in the past. It is worth emphasizing that the high crystallinity of the sample will be conducive to the characterization of its intrinsic physical properties. For comparison, we used a direct mixed assembly method to carry out high-pressure synthesis of the two nitrides, such as Figure 5As shown in (a)-(b), the crystal sizes of FeWN2 and FeMoN2 are close to 1 μm, much smaller than the crystals obtained by the layer-by-layer assembly method.
[0033] For the magnetic ternary nitrides FeWN2 and FeMoN2, the scale has a great influence on their magnetism. Therefore, we characterized their magnetism at low temperatures (1.8 K < T < 300 K). The experiment was carried out on a magnetic comprehensive measurement system (PPMS) produced by Quantum Design. Previous reports were usually based on the magnetic characterization of nano-samples, so they often included more size effects. We used the synthesized high-quality samples with a size of dozens of microns to characterize the magnetism of FeWN2 and FeMoN2. Figure 6 Figures (a) and (b) respectively show the field-cooled (FC) and zero-field-cooled (ZFC) temperature-dependent magnetization curves of FeWN2 and FeMoN2 under a background magnetic field of 1000 Oe. Their magnetism shows obvious differences from the reported results. For FeWN2, the antiferromagnetic phase transition point of the samples prepared by the present experimental method occurs near 50 K, much higher than the previously reported 27 K, indicating that the previously reported samples contained a large number of defects. In addition, when the temperature is lower than 25 K, the magnetic order of FeWN2 changes again, and an antiferromagnetic to ferromagnetic transition may occur, which can also be explained by Figure 7 the reciprocal of the magnetic susceptibility in (a) and Figure 8 the effective magnetic moment (μ eff ) of FeWN2 as a function of temperature in (a). Similarly, as shown in Figure 6 (b) and Figure 7 (b), the antiferromagnetic phase transition of FeMoN2 occurs at 71 K, slightly lower than the reported 75 K, and μ eff is close to 6 μ B (as shown in Figure 8 (b)), much higher than the previously reported magnetic saturation value. Therefore, the conclusion in previous reports that there are strong fluctuations in Mo atoms, which may suppress the nearest-neighbor exchange interaction between Fe-Fe and thus significantly reduce the total magnetic moment, is obviously wrong. There may be nitrogen vacancies in the previously reported crystal structure, and the existence of the N-2p and Fe-3d mixed state may lead to a significant reduction in the intrinsic magnetic moment of Fe in FeMoN2. The spin pairing effect may reduce the number of unpaired electrons in the Fe-3d energy level, thus reducing the magnetic moment of iron.
[0034] The above is a further detailed description of the present invention, which should not be regarded as a limitation to the specific implementation of the present invention. For those of ordinary skill in the technical field to which the present invention belongs, simple deductions or substitutions without departing from the concept of the present invention are within the protection scope of the present invention.
Claims
1. A rapid preparation method of ternary nitride, characterized in that: The following steps are involved: The ternary metal salt and excess sodium amide are charged in a layered manner of ternary metal salt-sodium amide-ternary metal salt, and then reacted at a pressure of 1 to 6 GPa to obtain a ternary nitride crystal corresponding to the ternary metal salt.
2. The rapid preparation method according to claim 1, characterized in that: The molar ratio of the ternary metal salt-sodium amide-ternary metal salt layers is 2.5:(1-1.05):2.
5.
3. The rapid preparation method according to claim 1, characterized in that: The diameter of the contact surface between each layer of the ternary metal salt-sodium amide-ternary metal salt is less than 10 mm.
4. The rapid preparation method according to claim 1, characterized in that: The ternary metal salt is selected from FeWO4 or FeMoO4.
5. The rapid preparation method according to claim 1, characterized in that: The reaction pressure is 2-5 GPa; and / or the reaction temperature is 800-1800°C.
6. The rapid preparation method according to claim 1, characterized in that: The reaction time is 1 to 5 minutes.
7. The rapid preparation method according to claim 1, characterized in that: The reactants are charged into a heat-resistant tube that does not participate in the reaction.
8. The rapid preparation method according to claim 7, characterized in that: The heat-resistant tube is selected from a salt tube and a hexagonal boron nitride tube.
9. The rapid preparation method according to claim 7 or 8, characterized in that: The wall thickness of the heat-resistant tube is greater than 1 mm.
10. The rapid preparation method according to any one of claims 1 to 8, characterized in that: The size of the prepared ternary nitride crystals is 1 to 50 μm.